2022
DOI: 10.1111/1750-3841.16140
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion effect on CCK and GLP‐1 release and antioxidant capacity of some plant‐based milk substitutes

Abstract: Recently, plant‐based milk substitutes, as an emerging industry, are receiving more attention. Despite that, these dairy alternatives have not been adequately studied for their functional properties. Thus, the current research was devoted to study the satiety potential through in vitro secretion of cholecystokinin (CCK) and glucagon‐like peptide‐1 (GLP‐1), and the antioxidant capacity of these dairy alternatives after in vitro digestion. The enteroendocrine cell line, STC‐1, was used to measure satiety hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…When comparing the four test products, both cow’s milk and soy drink exhibited the highest antioxidative attributes, and there were no statistically significant differences between these two beverages. As in the current study, Aly et al also measured the highest antioxidative capacity of the tested in vitro digested plant-based drinks of soy drink using ORAC and TEAC assays. Slightly higher values were revealed for soy drink than for cow’s milk considering the ORAC and TEAC assays.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…When comparing the four test products, both cow’s milk and soy drink exhibited the highest antioxidative attributes, and there were no statistically significant differences between these two beverages. As in the current study, Aly et al also measured the highest antioxidative capacity of the tested in vitro digested plant-based drinks of soy drink using ORAC and TEAC assays. Slightly higher values were revealed for soy drink than for cow’s milk considering the ORAC and TEAC assays.…”
Section: Discussionmentioning
confidence: 72%
“…However, the study tested undigested beverages, and the digestion appears to have a main influence on the antioxidative potential. Aly et al 31 showed, for example, that the total phenolic content in digested cow's milk and plant-based drinks was higher than in the undigested samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even an oat-based drink rich in β-glucans could be useful for controlling cholesterol levels [ 24 , 30 , 91 ]. Moreover, recent data suggest that spelt-based drinks may have an important satiating effect [ 92 ]. Furthermore, as in the case of diabetes, limiting the intake of any plant-based drink, which can cause large fluctuations in blood sugar and insulin (rice in particular [ 20 ]), could be beneficial.…”
Section: Advice In Specific Situationsmentioning
confidence: 99%